Surface treating agent, preparation method of surface treating agent, conductive glass fiber and preparation method of conductive glass fiber
By using surface treatment agents composed of modified carbon nanomaterials and aqueous epoxy resins, a conductive coating film is formed, which solves the problems of insufficient conductivity and complex process of glass fibers, and achieves good conductivity, high mechanical strength and resin Combining with strong ability.
Patent Information
- Application Number
- CN202411711150.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-18
AI Technical Summary
In the prior art, the conductive properties of glass fibers are insufficient, and the electroless plating process is complex and costly, resulting in limited production of conductive glass fibers.
A surface treatment agent is adopted, which consists of modified carbon nanomaterials, aqueous epoxy resin emulsions, epoxy silane coupling agents, etc., and forms a stable conductive coating by adjusting the pH value and the use of the modifier. Film, improves the conductivity and mechanical strength of glass fibers.
The conductive glass fiber has good conductivity, high mechanical strength and strong binding ability with resin, which solves the problems of insufficient conductivity and complex process in the prior art.
Smart Images

Figure CN119461891A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of glass fibers, and in particular to a surface treatment agent and a preparation method thereof, and a conductive glass fiber and a preparation method thereof. Background Art
[0002] As an ideal reinforcing material, glass fiber is used in all aspects of life due to its excellent corrosion resistance, high temperature resistance, low price, ultra-high strength and other characteristics, and occupies a very important position in the field of high-performance fibers.
[0003] At present, in order to meet the requirements of glass fiber conductivity, the surface of the glass fiber needs to be treated to reduce the resistivity of the glass fiber. In the related art, chemical plating is performed on the glass fiber to form a metal coating on the surface of the glass fiber, thereby improving its conductivity. However, when chemically plating the glass fiber, the glass fiber matrix needs to be roughened, sensitized and activated. The process is complicated, and the heavy metal target required in the activation process is expensive, which limits the further development of the preparation of conductive glass fiber by chemical plating.
[0004] In addition, since ordinary glass fiber is an inorganic non-metallic fiber, there are no active groups on its surface, which makes it difficult for metal materials to adhere to the surface of the glass fiber, and it is impossible to produce conductive fibers with excellent and stable conductive properties. In addition, the metal material attached to the surface of the glass fiber is not conducive to the combination of the glass fiber and the resin, resulting in poor bonding strength of the composite material and affecting the life of the material. Summary of the invention
[0005] In order to solve the above technical problems, the present application aims to provide a surface treatment agent and a preparation method thereof, a conductive glass fiber and a preparation method thereof. The conductive glass fiber treated with the surface treatment agent of the present application has the advantages of good conductivity, high mechanical strength and strong bonding ability with resin.
[0006] According to the first aspect of the present application, a surface treatment agent is provided, wherein the mass percentage of each component of the surface treatment agent to the total mass of the surface treatment agent is as follows:
[0007]
[0008]
[0009] Wherein, the conductive agent includes modified carbon nanomaterials.
[0010] In some embodiments of the present application, the modified carbon nanomaterial includes a carbon nanomaterial and a modifier, the modifier includes an amine modifier, and the carbon chain length of the amine modifier is greater than or equal to C10.
[0011] In some embodiments of the present application, the mass ratio of the carbon nanomaterial to the modifier is 1:0.5-2.0.
[0012] In some embodiments of the present application, the modifier includes a combination of one or more of dodecyldimethylbenzylammonium chloride and octadecyl-(2-sulfite)-ethyldimethylammonium;
[0013] The film former includes one or a combination of water-based epoxy resin emulsion and water-based polyurethane emulsion;
[0014] The coupling agent includes one of epoxy silane coupling agents and amino silane coupling agents or a combination of the two.
[0015] In some embodiments of the present application, the surface treatment agent further comprises:
[0016] A penetrant, the mass of which accounts for 0.5-2wt% of the total mass of the surface treatment agent;
[0017] and / or, a lubricant, wherein the mass of the lubricant accounts for 0.5-2wt% of the total mass of the surface treatment agent.
[0018] According to a second aspect of the present application, a method for preparing a surface treatment agent is provided. The method for preparing a surface treatment agent is used to prepare the surface treatment agent as described above, and the preparation method comprises:
[0019] Mixing the conductive agent, the film-forming agent, the coupling agent and the water to obtain a premix;
[0020] The pH value of the premix is adjusted to a preset value using a pH adjuster to obtain the surface treatment agent.
[0021] In some embodiments of the present application, the method for preparing the conductive agent includes:
[0022] Mixing the carbon nanomaterial with water to obtain a mixed solution;
[0023] Adding a modifier to the mixed solution, reacting under a first preset condition to obtain an intermediate;
[0024] The intermediate material is dried to obtain the conductive agent.
[0025] In some embodiments of the present application, the first preset condition includes: temperature of 60-85° C. and time of 0.5-2 h.
[0026] According to a third aspect of the present application, a conductive glass fiber is provided, comprising a glass fiber matrix and a surface treatment layer arranged on the surface of the glass fiber matrix, wherein the surface treatment layer is formed by the surface treatment agent as described above or by a surface treatment agent prepared by the preparation method of the surface treatment agent as described above.
[0027] According to a fourth aspect of the present application, a method for preparing a conductive glass fiber is provided. The method for preparing a conductive glass fiber is used to prepare the conductive glass fiber as described above. The method comprises:
[0028] Immersing the glass fiber substrate in the surface treatment agent and treating it under a third preset condition to obtain pretreated glass fiber;
[0029] The pretreated glass fiber is treated under a fourth preset condition to obtain the conductive glass fiber.
[0030] The technical solution provided by this application may have the following beneficial effects:
[0031] The surface treatment agent of the present application not only has stable carbon nanomaterial dispersibility, but also has the basis for reaction with film-forming agent and coupling agent, and can be used for surface treatment of glass fiber, and the modified carbon nanomaterial is used to reduce the surface resistance of glass fiber; through the action of film-forming agent, the surface treatment agent can be coated on the surface of glass fiber, and cooperate with modified carbon nanomaterial to form a conductive coating film, and improve the mechanical strength of glass fiber; through the action of coupling agent after pH adjustment, it can react with the hydroxyl group on the surface of glass fiber, and further promote the binding force between modified carbon nanomaterial, film-forming agent and glass fiber in the conductive coating film. In this way, the conductive glass fiber obtained by using the surface treatment agent of the present application has the advantages of good conductivity, high mechanical strength and strong ability to bind with resin.
[0032] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0034] Figure 1 is a flow chart of a method for preparing a surface treatment agent according to an exemplary embodiment.
[0035] Figure 2 is a flow chart of a method for preparing a conductive agent according to an exemplary embodiment.
[0036] Figure 3The figure is a schematic diagram of a cross-sectional structure of a conductive glass fiber according to an exemplary embodiment.
[0037] Figure 4 FIG. 4 is a surface morphology diagram of a conductive glass fiber according to an exemplary embodiment.
[0038] Figure 5 The present invention is a flow chart of a method for preparing conductive glass fiber according to an exemplary embodiment.
[0039] Figure 6a This is a photograph of the conductive agent in Preparation Example 1 after being left standing for 0 hours.
[0040] Figure 6b This is a photograph of the conductive agent in Preparation Example 1 after being left to stand for 24 hours. DETAILED DESCRIPTION
[0041] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme of the present application will be clearly and completely described below in combination with the embodiments of the present application and the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present application. It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments can be arbitrarily combined with each other.
[0042] The present application provides a surface treatment agent, the mass percentage of each component of the surface treatment agent to the total mass of the surface treatment agent is as follows: 1-5wt% conductive agent; 15-25wt% film-forming agent; 5-15wt% coupling agent; the balance is water; wherein the conductive agent includes modified carbon nanomaterials. The surface treatment agent of the present application not only has stable carbon nanomaterial dispersibility, but also has a basis for reaction with film-forming agent and coupling agent, and can be used for surface treatment of glass fiber, and the modified carbon nanomaterial is used to reduce the surface resistance of glass fiber; through the action of the film-forming agent, the surface treatment agent can be coated on the surface of the glass fiber, and cooperate with the modified carbon nanomaterial to form a conductive coating film, and improve the mechanical strength of the glass fiber; through the action of the coupling agent after pH adjustment, it can react with the hydroxyl group on the surface of the glass fiber, and can further promote the binding force between the modified carbon nanomaterial, the film-forming agent and the glass fiber in the conductive coating film. In this way, the conductive glass fiber obtained by using the surface treatment agent of the present application has the advantages of good conductivity, high mechanical strength and strong ability to bind with resin.
[0043] Some specific implementation modes described below are intended to facilitate those skilled in the art to understand the present embodiment, and the present embodiment is not limited to some specific implementation modes described below.
[0044] In an exemplary embodiment, the present application provides a surface treatment agent, and the mass percentage of each component of the surface treatment agent to the total mass of the surface treatment agent is as follows:
[0045]
[0046] Wherein, the conductive agent includes modified carbon nanomaterials.
[0047] Carbon nanomaterials are a class of nanoscale materials composed of carbon atoms, which can be carbon nanotubes, graphene, carbon black, etc. Carbon nanotubes (CNTs) are tubular structures formed by carbon atoms arranged in a hexagonal shape, and have excellent electrical conductivity, thermal conductivity and mechanical strength. Graphene is a two-dimensional material formed by a single layer of carbon atoms arranged in a hexagonal shape, which has extremely high surface area, excellent electrical conductivity, thermal conductivity and mechanical strength. Carbon black is a tiny particle composed of carbon atoms, which has a high specific surface area and good electrical conductivity. Using one or more combinations of carbon nanotubes, graphene or carbon black as a conductive agent can effectively reduce the surface resistivity of glass fibers, while increasing the roughness of the glass fiber surface and improving the interface bonding ability between glass fibers and resins.
[0048] The film-forming agent can form a uniform and continuous film after drying or curing, so as to cover the glass fiber. The film-forming agent can be, for example, acrylic acid, polyurethane, epoxy resin, etc.
[0049] The coupling agent usually contains two different functional groups, one functional group can form a chemical bond with an inorganic substance (such as glass fiber, carbon nanomaterial), and the other functional group can be compatible or reacted with an organic polymer film-forming agent to improve the interfacial bonding force between the conductive coating formed by the surface treatment agent on the surface of the glass fiber and the glass fiber. The coupling agent can be, for example, a silane coupling agent, a titanate coupling agent, an aluminate coupling agent, etc.
[0050] In this embodiment, the surface treatment agent not only has stable carbon nanomaterial dispersibility, but also has a basis for reacting with film-forming agents and coupling agents, and can be used for surface treatment of glass fibers, utilizing modified carbon nanomaterials to reduce the surface resistance of glass fibers; through the action of the film-forming agent, the surface treatment agent can be coated on the surface of the glass fibers, and cooperate with the modified carbon nanomaterials to form a conductive coating film, and enhance the mechanical strength of the glass fibers; through the action of the coupling agent after pH adjustment, it can react with the hydroxyl groups on the surface of the glass fibers, and further promote the bonding between the modified carbon nanomaterials in the conductive coating film, the film-forming agent, and the glass fibers.
[0051] For example, in one embodiment, the mass percentage of each component of the surface treatment agent to the total mass of the surface treatment agent is as follows:
[0052]
[0053] Wherein, the conductive agent includes modified carbon nanomaterials.
[0054] In another embodiment, the mass percentage of each component of the surface treatment agent to the total mass of the surface treatment agent is as follows:
[0055]
[0056] Wherein, the conductive agent includes modified carbon nanomaterials.
[0057] In another embodiment, the mass percentage of each component of the surface treatment agent to the total mass of the surface treatment agent is as follows:
[0058]
[0059] Wherein, the conductive agent includes modified carbon nanomaterials.
[0060] The surface treatment agent in this application is an emulsion-like substance, which is formed by dispersing a conductive agent, a film-forming agent, a coupling agent, etc. in water. In order to make the surface treatment agent have better comprehensive performance, in addition to controlling the content of each component in the surface treatment agent, it is also necessary to make each component able to maintain stability in water for a long time to avoid changes in the actual component content of the product due to precipitation or stratification of the components during use. Among them, due to the large specific surface area and low polarity of carbon nanomaterials, they are prone to agglomeration and stratification in water, affecting their dispersibility and stability in water.
[0061] Based on this, in an exemplary embodiment, the modified carbon nanomaterial includes a carbon nanomaterial and a modifier, the modifier includes an amine modifier, and the carbon chain length of the amine modifier is greater than or equal to C10.
[0062] In this embodiment, the modifier is a long carbon chain amine modifier with a carbon chain length greater than or equal to C10. When the carbon nanomaterial is treated with the modifier, on the one hand, the long carbon chain can be adsorbed on the surface of the carbon nanomaterial by non-covalent modification to improve the adhesion. The conductive agent thus formed can be stably dispersed in water. In the surface treatment agent of the aqueous system, it can remain stationary for more than 24 hours without stratification, thereby improving the stability of the surface treatment agent and its uniform distribution on the glass fiber surface. However, if a modifier without a long carbon chain or a short carbon chain is used, it is difficult to maintain the long-term dispersion stability of the carbon nanomaterial in water, and it is easy to form agglomerates on the surface of the glass fiber, affecting the conductivity and mechanical properties of the composite material. On the other hand, when the film-forming agent and the coupling agent are materials containing epoxy groups (such as epoxy resin), under the action of a pH adjuster, the amine group in the amine modifier reacts with the epoxy group in the film-forming agent and the coupling agent. The conductive coating film formed can improve the wear resistance of the conductive glass fiber and the adhesion of the carbon nanomaterial, thereby allowing the glass fiber to maintain conductivity for a longer period of time.
[0063] In an exemplary embodiment, the mass ratio of the carbon nanomaterial to the modifier is 1:0.5-2.0.
[0064] If the amount of modifier is too low, the dispersibility of carbon nanomaterials in water will decrease, affecting the uniformity of its distribution on the surface of glass fiber, easily causing interface defects, and affecting the current continuity on the surface of glass fiber, which is not conducive to the decrease of surface resistance of glass fiber; if the amount of modifier is too high, it will affect the chemical reaction between the surface treatment agent and the glass fiber, resulting in a decrease in the interface bonding force between the conductive coating and the glass fiber, and a decrease in wear resistance. Therefore, in this embodiment, by controlling the mass ratio of carbon nanomaterial to modifier to 1:0.5-2.0, the carbon nanomaterial can have good dispersibility in water, and the conductive coating can maintain a good interface bonding force with the glass fiber. Exemplarily, the mass ratio of carbon nanomaterial to modifier is 1:0.5, 1:0.8, 1:1, 1:1.5, 1:2.0.
[0065] In an exemplary embodiment, the modifier includes a combination of one or more of dodecyldimethylbenzyl ammonium chloride and octadecyl-(2-sulfite)-ethyldimethylammonium.
[0066] In this embodiment, the long-chain amine modifier can be dodecyldimethylbenzyl ammonium chloride and / or octadecyl-(2-sulfite)-ethyldimethylammonium. The above-mentioned modifiers can not only make the carbon nanomaterials maintain good dispersibility in water, but also make the conductive coating on the surface of the glass fiber have good wear resistance, thereby allowing the glass fiber to maintain long-term conductivity.
[0067] In an exemplary embodiment, the film former includes one or a combination of waterborne epoxy resin emulsion and waterborne polyurethane emulsion.
[0068] In this embodiment, the aqueous epoxy resin emulsion and the aqueous polyurethane emulsion have good dispersibility in water, so that each component of the surface treatment agent has good dispersion stability. The film-forming agent can be selected from one of the aqueous epoxy resin emulsion and the aqueous polyurethane emulsion, or the aqueous epoxy resin emulsion and the aqueous polyurethane emulsion can be compounded according to a mass ratio of 2:1. Among them, the aqueous epoxy resin emulsion can be a model such as 5522-1, EP-51, etc. The aqueous polyurethane emulsion can be PU-601 or 8081.
[0069] In an exemplary embodiment, the coupling agent includes one or a combination of an epoxy silane coupling agent and an amino silane coupling agent.
[0070] Silane coupling agent is an organosilicon compound that can improve the bonding force between the conductive coating formed by the surface treatment agent and the glass fiber. In this embodiment, the coupling agent can be one of an epoxy silane coupling agent and an amino silane coupling agent, or the epoxy silane coupling agent and the amino silane coupling agent can be compounded in a mass ratio of 2:1. Among them, the epoxy silane coupling agent can be, for example, a composition of one or more of 3-glycidyloxypropyl triethoxysilane, 3-glycidyloxypropyl trimethoxysilane, 3-glycidyloxypropyl methyl dimethoxysilane, and 3-glycidyloxypropyl methyl diethoxysilane. The amino silane coupling agent can be, for example, a composition of one or two of γ-aminopropyl triethoxysilane and γ-aminopropyl trimethoxysilane.
[0071] In an exemplary embodiment, the surface treatment agent further comprises:
[0072] Penetrant, the mass of the penetrant accounts for 0.5-2wt% of the total mass of the surface treatment agent;
[0073] and / or, a lubricant, the mass of the lubricant accounting for 0.5-2wt% of the total mass of the surface treatment agent.
[0074] In this embodiment, by adding a penetrant to the surface treatment agent, the surface energy of the surface treatment agent can be reduced, the wettability and adhesion of the surface treatment agent to the glass fiber can be improved, and the surface polarity and reactivity of the conductive glass fiber can also be enhanced. For example, the mass of the penetrant accounts for 0.5wt%, 1wt% or 2wt% of the total mass of the surface treatment agent. The penetrant can be, for example, a JFC type fatty alcohol polyoxyethylene ether.
[0075] By adding a lubricant to the surface treatment agent, the continuity and uniformity of the conductive coating formed on the surface of the glass fiber can be improved, and the bundling and processing performance of the glass fiber can be improved. Exemplarily, the mass of the lubricant accounts for 0.5wt%, 1wt% or 2wt% of the total mass of the surface treatment agent. The lubricant can be polyethylene glycol, and the polyethylene glycol can be, for example, PEG-400, PEG-800, PEG-1000, etc.
[0076] In an exemplary embodiment, if Figure 1 As shown, the present application provides a method for preparing a surface treatment agent, comprising:
[0077] S110, mixing a conductive agent, a film-forming agent, a coupling agent and water to obtain a premix.
[0078] In step S110, the conductive agent, the film-forming agent, the coupling agent and water are mixed uniformly at a temperature of 25° C. to obtain a premix. In order to reduce the influence of impurity ions on the performance of the surface treatment agent, the water in this embodiment can be deionized water.
[0079] S120, adjusting the pH value of the premix to a preset value using a pH adjusting agent to obtain a surface treatment agent.
[0080] In step S120, the preset value may be weak acidity, such as a pH value of 4-6. The surface treatment agent at this pH is beneficial to the reaction of the modified carbon nanomaterial with the film-forming agent and the coupling agent, and at the same time improves its reaction with the hydroxyl groups on the surface of the glass fiber to form a stronger chemical bond; on the other hand, it can also improve the stability of the surface treatment agent and reduce the occurrence of precipitation or stratification. The pH adjusting agent may be, for example, one or more combinations of citric acid, oleic acid, glacial acetic acid, etc.
[0081] In an exemplary embodiment, if Figure 2 As shown, the preparation method of the conductive agent includes:
[0082] S210, mixing the carbon nanomaterial with water to obtain a mixed solution.
[0083] In step S210, the mass ratio of the carbon nanomaterial to water may be 1:2-5, for example, the mass ratio of the carbon nanomaterial to water is 1:2, 1:3 or 1:5.
[0084] S220, adding a modifier to the mixed solution, reacting under the first preset condition to obtain an intermediate.
[0085] In step S220, the first preset condition may be 60-85°C and the time may be 0.5-2h. For example, the first preset condition may be 60°C and the time may be 2h; the first preset condition may be 80°C and the time may be 1h; the first preset condition may be 85°C and the time may be 0.5h.
[0086] S230, drying the intermediate to obtain a conductive agent.
[0087] In step S230, after obtaining the intermediate, the water therein is filtered to obtain a precipitate; and the precipitate is dried to obtain a conductive agent.
[0088] In an exemplary embodiment, if Figure 3 As shown, the present application provides a conductive glass fiber, which includes a glass fiber matrix 1 and a surface treatment layer 2 arranged on the surface of the glass fiber matrix 1, and the surface treatment layer 2 is formed by the above surface treatment agent or a surface treatment agent prepared by the above surface treatment agent preparation method.
[0089] In this embodiment, the surface treatment layer 2 is the conductive coating film mentioned above. The surface treatment layer 2 is formed by coating the glass fiber matrix 1 to obtain a conductive glass fiber with conductive properties.
[0090] The surface morphology of the conductive glass fiber in this embodiment is as follows Figure 4 As shown, according to Figure 4 It can be seen that the surface of the glass fiber is an obviously rough surface, which indicates that the surface of the conductive glass fiber in this embodiment has a surface treatment layer 2 .
[0091] In an exemplary embodiment, if Figure 5 As shown, the present application provides a method for preparing a conductive glass fiber, comprising:
[0092] S310, immersing the glass fiber substrate in a surface treatment agent, and treating it under a second preset condition to obtain a pretreated glass fiber.
[0093] In step S310, the second preset condition includes: temperature of 20-30°C, and immersion time of 5-20s. For example, the second preset condition is: temperature of 20°C, and immersion time of 20s; the second preset condition is: temperature of 25°C, and immersion time of 10s; the second preset condition may be: temperature of 30°C, and immersion time of 5s.
[0094] S320, treating the pretreated glass fiber under a third preset condition to obtain a conductive glass fiber.
[0095] In step S320, the third preset condition includes: first treating at a temperature of 100-120°C for 5-10 minutes, and then treating at a temperature of 145-155°C for 5-10 minutes. The first treatment at a temperature of 100-120°C can avoid high-temperature decomposition of the film-forming agent, promote the reaction of the coupling agent with the hydroxyl group on the surface of the glass fiber, and the reaction of the conductive agent with the film-forming agent and the coupling agent; and the second treatment at a temperature of 145-155°C can promote further reactions between the components to form stronger chemical bonds.
[0096] Illustratively, in one embodiment, the third preset condition includes: first treating at a temperature of 110° C. for 10 min, and then treating at a temperature of 145° C. for 10 min.
[0097] In another embodiment, the third preset condition includes: first treating at a temperature of 100° C. for 8 minutes, and then treating at a temperature of 150° C. for 8 minutes.
[0098] In another embodiment, the third preset condition includes: first treating at a temperature of 120° C. for 5 minutes, and then treating at a temperature of 155° C. for 5 minutes.
[0099] The specific implementation methods of the present application are further described below in conjunction with preferred embodiments, and examples of preferred value ranges of each component in the surface treatment agent provided in the present application are explained in detail.
[0100] Preferred Example 1
[0101] A surface treatment agent, the mass percentage of each component of the surface treatment agent to the total mass of the surface treatment agent is as follows:
[0102]
[0103] The conductive agent includes carbon nanomaterials and a modifier, the modifier includes an amine modifier, and the carbon chain length of the amine modifier is greater than or equal to C10.
[0104] Preferred Example 2
[0105] A surface treatment agent, the mass percentage of each component of the surface treatment agent to the total mass of the surface treatment agent is as follows:
[0106]
[0107] The conductive agent includes carbon nanomaterials and modifiers, the modifiers include amine modifiers, and the carbon chain length of the amine modifiers is greater than or equal to C10; the mass ratio of the carbon nanomaterials to the modifiers is 1:0.5-2.0.
[0108] Preferred Example 3
[0109] A surface treatment agent, the mass percentage of each component of the surface treatment agent to the total mass of the surface treatment agent is as follows:
[0110]
[0111] The conductive agent includes a carbon nanomaterial and a modifier, and the mass ratio of the carbon nanomaterial to the modifier is 1:0.5-2.0;
[0112] The modifier includes a combination of one or more of dodecyldimethylbenzyl ammonium chloride and octadecyl-(2-sulfite)-ethyldimethylammonium;
[0113] Film formers include waterborne epoxy resin emulsions;
[0114] The coupling agent includes a silane coupling agent.
[0115] Preferred Example 4
[0116] A surface treatment agent, the mass percentage of each component of the surface treatment agent to the total mass of the surface treatment agent is as follows:
[0117]
[0118] The conductive agent includes a carbon nanomaterial and a modifier, and the mass ratio of the carbon nanomaterial to the modifier is 1:0.5-2.0;
[0119] The modifier includes a combination of one or more of dodecyldimethylbenzyl ammonium chloride and octadecyl-(2-sulfite)-ethyldimethylammonium;
[0120] Film formers include waterborne epoxy resin emulsions;
[0121] The coupling agent includes a silane coupling agent.
[0122] Preferred Example 5
[0123] A surface treatment agent, the mass percentage of each component of the surface treatment agent to the total mass of the surface treatment agent is as follows:
[0124]
[0125] The conductive agent includes a carbon nanomaterial and a modifier, and the mass ratio of the carbon nanomaterial to the modifier is 1:0.8-1.5;
[0126] The modifier includes a combination of one or more of dodecyldimethylbenzyl ammonium chloride and octadecyl-(2-sulfite)-ethyldimethylammonium;
[0127] Film formers include waterborne epoxy resin emulsions;
[0128] The coupling agent includes a silane coupling agent.
[0129] The preparation method of the surface treatment agent of preferred examples 1 to 5 comprises:
[0130] Mixing a conductive agent, a film-forming agent, a coupling agent and water to obtain a premix;
[0131] The pH value of the premix is adjusted to a preset value using a pH adjuster to obtain a surface treatment agent.
[0132] The preparation method of the conductive agent comprises:
[0133] mixing the carbon nanomaterial with water to obtain a mixed solution;
[0134] Adding a modifier to the mixed solution, reacting under a first preset condition to obtain an intermediate material;
[0135] The intermediate material is dried to obtain a conductive agent.
[0136] In order to more clearly explain the technical solution of the present application, the present application lists specific embodiments of the surface treatment agent and the conductive glass fiber, and the beneficial effects of selecting the above ranges of the content of each component will be explained by giving specific experimental data through specific embodiments. It should be noted that the raw material components and contents of the surface treatment agent in the embodiments of the present application do not limit the protection scope of the present application.
[0137] Preparation Example
[0138] It should be noted that, unless otherwise specified, the raw materials in the following preparation examples can be obtained from commercial sources. The carbon nanomaterial can be a carbon nanotube and graphene in a mass ratio of 1:1.
[0139] Preparation Example 1: A method for preparing a conductive agent, comprising the following steps:
[0140] The carbon nanomaterial is mixed with water to obtain a mixed solution; a modifier is added to the mixed solution, and the mixture is reacted at a temperature of 80°C for 1.5 hours to obtain an intermediate; the intermediate is cooled and filtered to obtain a precipitate, and the precipitate is dried to obtain a conductive agent. The modifier is dodecyl dimethyl benzyl ammonium chloride; and the weight ratio of the carbon nanomaterial, the modifier and water is 1:0.5:3.
[0141] After the unmodified carbon nanomaterial and the modified carbon nanomaterial (i.e., the conductive agent) were mixed with water, their stability was observed after standing for 0 h and 24 h. Figure 6a and Figure 6b It can be seen that after the carbon nanomaterials are modified in this preparation example, the obtained conductive agent can be stably dispersed in water and can remain unstratified for 24 hours, indicating that the conductive agent in this preparation example can maintain good dispersion stability in the surface treatment agent of the aqueous system.
[0142] In order to more clearly explain the technical solution of the present application, the present application also lists Preparation Examples 2-5 of the conductive agent, wherein the formula of Preparation 2-5 is shown in Table 1. It should be noted that, except for the parameters listed in Table 1, the other parameters of Preparation Example 2-5 are basically the same as those of Preparation Example 1.
[0143] Wherein, the ratio C1 is the mass ratio of dodecyldimethylbenzylammonium chloride to octadecyl-(2-sulfite)-ethyldimethylammonium.
[0144] The ratio C2 is the mass ratio of the carbon nanomaterial to the modifier.
[0145] The conductive agent prepared by the method of each preparation example was mixed with water and allowed to stand for 0 h, 24 h, 48 h, 72 h, and 96 h, and the system was observed to see whether precipitation, stratification, etc. occurred. The observation results were recorded in Table 1.
[0146] Table 1 Conductive agent formula and stability test table
[0147]
[0148] Note: “√” in Table 1 indicates that this modifier is used, and “ / ” indicates that this modifier is not used.
[0149] It can be seen from the data in Table 1 that the carbon nanomaterial treated with the modifier in the preparation example can significantly improve its dispersibility in water, and as the amount of the modifier increases, the retention time of the dispersion stability of the carbon nanomaterial in water is prolonged. Among them, when the mass ratio of the carbon nanomaterial to the modifier is 1:1.0-2.0, the modified carbon nanomaterial can maintain a long-term dispersion stability in water.
[0150] Example
[0151] It should be noted that, unless otherwise specified, the raw materials in the following examples can be obtained from the market. Among them, the film-forming agent in the following examples can be bisphenol A epoxy resin emulsion; the silane coupling agent can be 3-glycidyloxypropyl triethoxysilane; the penetrant can be JFC fatty alcohol polyoxyethylene ether; the lubricant can be polyethylene glycol; and the pH regulator can be oleic acid.
[0152] Embodiment 1: A method for preparing a surface treatment agent comprises the following steps:
[0153] (1) 1.0 wt% of a conductive agent, 15 wt% of a film-forming agent, 5 wt% of a coupling agent, 0.5 wt% of a penetrant, 0.5 wt% of a lubricant and 78.0 wt% of water were mixed and stirred at 25° C. to obtain a premix; wherein the conductive agent was prepared according to Preparation Example 1.
[0154] (2) The pH value of the premix is adjusted to 6 using a pH adjuster to obtain a surface treatment agent.
[0155] In order to more clearly explain the technical solution of the present application, the present application also lists Examples 2-14 of the preparation method of the surface treatment agent, wherein the formulas of Examples 2-14 are shown in Table 2.
[0156] Table 2 shows a specific example of the preparation method of the surface treatment agent in the present application. It should be noted that, except for the parameters listed in Table 2, other parameters of Examples 2-14 and Example 1 are substantially the same.
[0157] Among them, the ratio C3 is the mass ratio of the conductive agent, the coupling agent, and the film-forming agent.
[0158] Table 2 Formulation of surface treatment agent raw materials (unit: wt%)
[0159] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Conductive agent 1.0 2.0 2.0 2.0 3.0 3.0 4.0 Film former 15 19 19 19 20 22 22 Silane coupling agent 5 10 10 10 8 12 10 Penetrant 0.5 1.0 1.0 1.0 1.2 1.4 1.8 Lubricants 0.5 1.0 1.0 1.0 1.4 1.2 1.5 water 78.0 67.0 67.0 67.0 66.4 60.4 60.7 Ratio C3 1:5:15 1:5:9.5 1:5:9.5 1:5:9.5 1:2.7:6.7 1:4:7.3 1:3:5 Source of Conductive Agent Preparation Example 2 Preparation Example 3 Preparation Example 4 Preparation Example 5 Preparation Example 4 Preparation Example 2 Preparation Example 3
[0160] Table 2 (Continued) Formulation of surface treatment agent raw materials (Unit: wt%)
[0161] Example 8 Example 9 Example 10 Embodiment 11 Example 12 Embodiment 13 Embodiment 14 Conductive agent 5.0 2.0 2.5 3.0 3.5 3.5 4.0 Film former 25 21 18 16 20 24 16 Silane coupling agent 15 6 12 8 8 5 15 Penetrant 2.0 1.0 1.2 0.8 0.6 1.4 2.0 Lubricants 2.0 0.8 1.0 1.2 1.5 0.8 2.0 water 51.0 69.2 65.3 71.0 66.4 66.3 61.0 Ratio C3 1:3:5 1:3:10.5 1:4.8:7.2 1:2.7:5.3 1:2.3:5.7 1:1.4:6.9 1:3.8:4 Source of Conductive Agent Preparation Example 1 Preparation Example 1 Preparation Example 3 Preparation Example 3 Preparation Example 2 Preparation Example 2 Preparation Example 4
[0162] Performance Testing
[0163] According to the following method, the surface treatment agent in the above embodiment is used to prepare conductive glass fiber and conductive glass fiber fabric reinforced epoxy resin composite material. The preparation method of conductive glass fiber includes:
[0164] The glass fiber substrate was immersed in the surface treatment agent at a temperature of 25° C. for 10 seconds to obtain a pretreated glass fiber. The pretreated glass fiber was first kept at a temperature of 120° C. for 10 minutes and then kept at a temperature of 150° C. for 10 minutes to obtain a conductive glass fiber.
[0165] The conductive glass fiber is prepared into a fabric and then vacuum infused to obtain a conductive glass fiber fabric reinforced epoxy resin composite material.
[0166] According to the following method, the properties of the conductive glass fiber and the composite material made of the conductive glass fiber, the untreated glass fiber (recorded as comparative example 1), the glass fiber added with the unmodified carbon nanomaterial conductive agent (recorded as comparative example 2) and the composite material made of the untreated glass fiber were tested, and the test results are recorded in Table 3. Among them, Examples 1-14 in Table 3 refer to the conductive glass fibers or composite materials prepared by using the surface treatment agents of Examples 1-14.
[0167] 1. Resistivity: According to the method in GB / T 32993-2016 "Determination of volume resistivity of carbon fiber", the resistivity of conductive glass fiber is tested. The smaller the resistivity, the better the conductive performance of the conductive glass fiber.
[0168] 2. Wear resistance: Take a certain length of conductive glass fiber, tie a 5g weight to one end of the conductive glass fiber and fix it on the FFZ622 yarn wear resistance tester. After wrapping cotton cloth on the friction roller of the tester, rub the conductive glass fiber repeatedly for 50 times, record the mass after friction, and calculate its weight loss rate. The lower the weight loss rate, the better the wear resistance, and the stronger the bonding force between the surface treatment layer and the glass fiber matrix.
[0169] 3. Mechanical properties: The interlaminar shear strength, in-plane shear strength and tensile strength of the conductive glass fiber fabric reinforced epoxy resin composite material were tested according to ISO14130, ASTM D7078 and ISO527-5 respectively.
[0170] Table 3 Performance test table of conductive glass fiber and composite materials
[0171]
[0172] Table 3 (Continued) Performance test table of conductive glass fiber and composite materials
[0173]
[0174] Combining the data in Table 2 and Table 3, it can be seen that the resistivity of the glass fiber treated with the surface treatment agent of the present application is significantly reduced, indicating that it has good conductivity. After rubbing the conductive glass fiber 50 times, its weight loss rate is within 10%, indicating that it has good wear resistance and good bonding between the surface treatment layer and the glass fiber matrix. Compared with the composite material prepared from untreated glass fiber, the composite material prepared using the conductive glass fiber of the present application has more excellent mechanical properties, indicating that the surface treatment agent of the present application can also improve the mechanical strength of the glass fiber.
[0175] In addition, it can be seen from the data in Table 2 and Table 3 that Examples 2-3, Examples 6-7 and Example 10 have better comprehensive performance. Therefore, by adjusting the mass percentage of each component of the surface treatment agent, when the conductive agent is 2-4wt%; the film-forming agent is 18-22wt%; the coupling agent is 8-12wt%; the penetrant is 1.0-1.8wt%; the lubricant is 1.0-1.5wt%, the mass ratio of the carbon nanomaterial and the modifier in the conductive agent is 1:0.8-1.5, and the mass ratio of the conductive agent, the silane coupling agent, and the film-forming agent is 1:3-5:5-9.5, the components of the surface treatment agent can maintain good dispersion stability, and the conductive glass fiber prepared by the surface treatment agent and the composite material prepared by the conductive glass fiber can have better mechanical properties.
[0176] It should be noted that, in this article, the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0177] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application is described in detail with reference to the above embodiments, a person skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present application.
Claims
1. A surface treatment agent, characterized in that: The percentage of the mass of each component of the surface treatment agent to the total mass of the surface treatment agent is as follows: Wherein, the conductive agent includes modified carbon nanomaterials.
2. The surface treatment agent according to claim 1, characterized in that The modified carbon nanomaterial comprises a carbon nanomaterial and a modifier, wherein the modifier comprises an amine modifier, and the carbon chain length of the amine modifier is greater than or equal to C10.
3. The surface treatment agent according to claim 2, characterized in that The mass ratio of the carbon nanomaterial to the modifier is 1:0.5-2.
0.
4. The surface treatment agent according to claim 2, characterized in that The modifier includes a combination of one or more of dodecyldimethylbenzylammonium chloride and octadecyl-(2-sulfite)-ethyldimethylammonium; The film-forming agent includes one of water-based epoxy resin emulsion and water-based polyurethane emulsion or a combination of the two; The coupling agent includes one of epoxy silane coupling agents and amino silane coupling agents or a combination of the two.
5. The surface treatment agent according to any one of claims 1 to 4, characterized in that: The surface treatment agent also includes: A penetrant, the mass of which accounts for 0.5-2wt% of the total mass of the surface treatment agent; and / or, a lubricant, wherein the mass of the lubricant accounts for 0.5-2wt% of the total mass of the surface treatment agent.
6. A method for preparing a surface treatment agent, characterized in that: The preparation method of the surface treatment agent is used to prepare the surface treatment agent according to any one of claims 1 to 5, and the preparation method comprises: Mixing the conductive agent, the film-forming agent, the coupling agent and the water to obtain a premix; The pH value of the premix is adjusted to a preset value using a pH adjuster to obtain the surface treatment agent.
7. The method for preparing a surface treatment agent according to claim 6, characterized in that: The preparation method of the conductive agent comprises: Mixing the carbon nanomaterial with water to obtain a mixed solution; Adding a modifier to the mixed solution, reacting under a first preset condition to obtain an intermediate; The intermediate material is dried to obtain the conductive agent.
8. The method for preparing a surface treatment agent according to claim 7, characterized in that: The first preset conditions include: temperature of 60-85° C. and time of 0.5-2 h.
9. A conductive glass fiber, characterized in that: The conductive glass fiber includes a glass fiber matrix and a surface treatment layer arranged on the surface of the glass fiber matrix, and the surface treatment layer is formed by the surface treatment agent according to any one of claims 1 to 5 or a surface treatment agent prepared by the preparation method of the surface treatment agent according to any one of claims 6 to 8.
10. A method for preparing a conductive glass fiber, characterized in that: The method for preparing the conductive glass fiber is used to prepare the conductive glass fiber as claimed in claim 9, and the method comprises: Immersing the glass fiber substrate in the surface treatment agent and treating it under a second preset condition to obtain a pretreated glass fiber; The pretreated glass fiber is treated under a fourth preset condition to obtain the conductive glass fiber.